Transformation of global value chains under the influence of innovative technologies (Economics and region, 2023)
The article is devoted to the study of the process of transformation of global value chains under the influence of the development of technological processes. The paper compares the classical value chain based on and its configurations under the influence of advanced digital international production networks; development of robotics and artificial intelligence; additive manufacturing (3D printing). These innovation factors are proof that thanks to the change in the technological base of production, the innovation model will change as well, in which advanced achievements will have a decentralized nature and the possibility to arise at any stage of the production process. But there has not yet been a general return of parent company production back to the US or Europe, and this is unlikely to be an effective response to most of the risks that have emerged so far, with global value chains trending upwards rather than downwards. All the mentioned factors are proof that thanks to the change in the technological base of production, the innovation model will also change, in which advanced achievements will have a decentralized nature and the possibility to arise at any stage of the production process. The high frequency of transactions and mutual exchange between individual components of the innovation process, dispersed in international space along the global value chain, require increased coordination, which leads to an increase in transaction costs. There are also problems of intellectual property protection that arise when cooperating within the global value chain with representatives of countries in which institutions for their specification and protection are not sufficiently developed. In addition to the above, author considers it necessary to add to this list another group of factors related to the effect of global transactional risks. Global processes involving national economic systems expose them to risks with a large share of uncertainty, as it is difficult or impossible to predict and take measures to mitigate unforeseen negative consequences. A look at the trends in global production processes shows that innovative development and its connection with global value chains is a cyclical process in which the directions of alternating attraction of advanced technologies to greater openness and simultaneous closure to preserve the profitability of TNCs and national security are formed.
Keywords: global value chains; intangible assets; innovation; innovative development; technology; smile curve; stages of production; transnational corporations